Exit Interviews: The Impact of Perceived Sensitivity and Perceived Threat on Individuals’ Willingness to Disclose - Skeaton, Susan Givens; Ford, Lucy R. (Journal of Organizational Psychology, 2018)
For the results of exit interviews to make a difference they must reveal the true causes of voluntary turnover. Obtaining accurate exit interview data is challenging because departing employees often distort responses. This study had two purposes: (1) to create a scale of “information type” whereby potential reasons for leaving were evaluated for degree of sensitivity and threat; and (2) to determine whether information that is perceived as highly sensitive or threatening would be less likely to be disclosed. Our findings indicate that job context is perceived as less sensitive and threatening than interpersonal issues, which are less likely to be disclosed.